PIK3CA Mutation in HPV-Associated OPSCC Patients Receiving Deintensified Chemoradiation. (20th November 2019) - Beaty, Brian T; Moon, Dominic H; Shen, Colette J; Amdur, Robert J; Weiss, Jared; Grilley-Olson, Juneko; Patel, Shetal; Zanation, Adam; Hackman, Trevor G; Thorp, Brian; Blumberg, Jeffrey M; Patel, Samip N; et al.
Abstract: PIK3CA is the most frequently mutated gene in human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (OPSCC). Prognostic implications of such mutations remain unknown. We sought to elucidate the clinical significance of PIK3CA mutations in HPV-associated OPSCC patients treated with definitive chemoradiation (CRT). Seventy-seven patients with HPV-associated OPSCC were enrolled on two phase II clinical trials of deintensified CRT (60 Gy intensity-modulated radiotherapy with concurrent weekly cisplatin). Targeted next-generation sequencing was performed. Of the 77 patients, nine had disease recurrence (two regional, four distant, three regional and distant). Thirty-four patients had mutation(s) identified; 16 had PIK3CA mutations. Patients with wild-type- PIK3CA had statistically significantly higher 3-year disease-free survival than PIK3CA -mutant patients (93.4%, 95% confidence interval [CI] = 85.0% to 99.9% vs 68.8%, 95% CI = 26.7% to 89.8%; P = .004). On multivariate analysis, PIK3CA mutation was the only variable statistically significantly associated with disease recurrence (hazard ratio = 5.71, 95% CI = 1.53 to 21.3; P = .01). PIK3CA mutation is associated with worse disease-free survival in a prospective cohort of newly diagnosed HPV-associated OPSCC patients treated with deintensified CRT.